Standardization of Required Level Probability of No-Failure Operation of the Building Envelopes by the Criterion of Total Thermal Resistance - Semko, Volodymyr; Leshchenko, Maryna; Cherednikova, Oleksandra (International Journal of Engineering and Technology, 2018)
The paper provides analysis of the state of the building envelope thermal reliability issue in Ukraine. It has been found that ensuring the reliability of the building envelope results only in economic losses and is not related to human losses, and therefore the question of normalization of no-failure performance probability of the construction upon the criterion of insufficient value of the reduced total thermal resistance is purely economic. The paper develops normalization of the required level of building envelope no-failure performance probability upon the criterion of reduced total thermal resistance. The suggested method of the required level standardization of building envelope no-failure performance probability upon the criterion of insufficient value of the reduced total thermal resistance of building envelope is proposed for the developers of normative documents, state standards, company standards or technical specifications. Designers should use only the calculated and average values of the minimum permissible thermal resistance, specified in the above-mentioned documents.Â Â